The Millennials of Tulancingo, Hidalgo, and E-commerce (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2019)
The present research aims to understand the level of usage and preferences of the Millennial Generation in the Municipality of Tulancingo, Hidalgo, regarding E-commerce, to be considered as a sales strategy, specifically focusing on three aspects: sociodemographic data, factors related to the use of mobile devices, and factors related to E-commerce. This is a mixed-method research, analyzing a sample of 382 surveys applied to Millennials native to this municipality, whose birth years range between 18 and 38, demonstrating that the use of technology among this generation is integrated into their daily lives, mainly in the acquisition and use of smartphones, indicated as their preferred mobile devices. They show a positive attitude towards E-commerce to purchase products and/or services, making it a viable sales strategy, provided that an analysis of the payment method is carried out. Despite a large portion of the respondents perceiving online purchases as secure, consideration should be given to the payment method strategy, ensuring security and trust for this generation.